Integrating computational thinking and creativity in project-based learning: A systematic review - Wenny Pinta Litna Tarigan; P. Paidi; Antuni Wiyarsi (Research and Development in Education (RaDEn), 2025)
In recent years, educators have faced challenges in designing learning that can improve students' computational thinking and creativity, especially in science and mathematics learning. This systematic review examines didactic research published between 2010 and 2023, following PRISMA guidelines. Relevant studies were identified through database searches in Scopus, Web of Science, and ERIC, using keywords related to computational thinking, creativity, science and math education. Twenty-five studies were selected for in-depth analysis through a structured screening process. These studies focus on strategies, methodologies, and assessment techniques that promote computational thinking (CT) and creativity in science and math classrooms. Particular emphasis is placed on project-based learning (PjBL) as a pedagogical framework for integrating CT and creativity into the learning process. The findings highlight how PjBL not only supports students in developing logical and systematic problem-solving skills but also fosters creative expression through open-ended, collaborative tasks. The review further explores tools and resources that enhance CT instruction and discusses how digital technologies can support creativity in science learning. The evidence highlights the effectiveness of integrating CT and creativity through PjBL within the context of science and math education.